HUBUNGAN BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA BOYOLALI - INDROPRASETYO , EKO (2011)
Human resource in organization is important determinant factor to run effectively activities in organization. A successful and performance in their job is determined by organization culture, commitment toward job field and satisfaction feel in working. The objectives of this research are 1) to analize the significance influence of organization culture toward the performance appraisal in KPP Pratama Boyolali, 2) to analize the significance influence of commitment toward the performance appraisal in KPP Pratama Boyolali 3) to analize the significance influence of job satisfaction toward the performance appraisal in KPP Pratama Boyolali 4) to analize the significance influence of organization culture, commitment, and job satisfaction toward the performance appraisal in KPP Pratama Boyolali . Research location used is Kantor Pelayanan Pajak Pratama Boyolali. Population and sample are the official of KPP Pratama Boyolali ad 68 or the entire of official. Source of data found from primary and secondary data. Data is collected by using questionnaire about organization culture, commitment, job satisfaction and official performance. The result of data is analized by using double regression linier technique. The result of analize shows that: (1) Variabel of organization culture partially influence significance toward performance appraisal. (2) Variabel of commitment partially influence significance toward performance appraisal. (3) Variabel of job satisfaction partially do not influence toward performance appraisal. (4) Variabel of organization culture, commitment, and job satisfaction influence toward performance appraisal.